2020
DOI: 10.1002/csc2.20019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hybrid wheat yield in Nebraska

Abstract: For hybrid wheat (Triticum aestivum L.) to be successful in the Great Plains, goodquality hybrid seed production must be reliable, and hybrid yield must exceed best commercial inbred cultivars (commercial heterosis). This research evaluates hybrid wheat cultivars developed from a full diallel of 26 parents that were planted in an augmented design at three locations in Nebraska in each of two years. The effects of using chemical hybridization were evaluated by testing the parents against hybrids that were creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The main target of the hybrid breeding program was to identify potential parents that can be crossed to produce F1 hybrids with a high heterosis level. Previous studies have reported important heterosis and heterobeltiosis in wheat [13,[35][36][37][38]. In this study, several hybrids exhibited significant heterosis and heterobeltiosis for the evaluated traits.…”
Section: Hybrid Performance and Heterosismentioning
confidence: 51%
“…The main target of the hybrid breeding program was to identify potential parents that can be crossed to produce F1 hybrids with a high heterosis level. Previous studies have reported important heterosis and heterobeltiosis in wheat [13,[35][36][37][38]. In this study, several hybrids exhibited significant heterosis and heterobeltiosis for the evaluated traits.…”
Section: Hybrid Performance and Heterosismentioning
confidence: 51%
“…These effects may be due to the nuclear genes (maternal effect) and cytoplasmic genes (non-maternal effect) (Barata et al 2019). Easterly et al (2020), who studied 650 F 1 combinations of wheat, reported an insignificant reciprocal effect in grain yield. Pelegrin et al (2020), who studied F 2 populations of wheat with a partial diallel crossing design (5 × 5), reported a significant reciprocal effect for the trait grain weight per plant.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…The exploitation of highlevel heterosis through different hybrid systems appears more promising than ever. Easterly Plants 2021, 10, 895 2 of 16 et al [3] reported mid-parent heterosis for grain yield of up to 24% for hybrids developed using chemical hybridization agent (CHA), demonstrating that F1 hybrid cultivars are able to outperform inbred varieties and ensure greater economic yield. However, without baseline studies to identify parental combinations for an efficient cross-pollination system, hybrid wheat will not be attractive commercially.…”
Section: Introductionmentioning
confidence: 99%